2003
DOI: 10.1029/2003jd003492
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to estimating the albedo for snow‐covered surfaces in the satellite UV method

Abstract: [1] This paper describes a new method for estimating snow albedo for satellite retrieval of surface UV irradiance and daily UV doses over snow-covered terrains. The method is based on combining satellite and meteorological analysis data. The satellite data exploited in this work are the measured reflectivities of the Total Ozone Mapping Spectrometer/ Nimbus 7 instrument that coincides with the European Centre for Medium-Range Weather Forecasts ERA-15 reanalyzed meteorological data. We compared satellite-retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Vast regions experience seasonal snow: in the Northern Hemisphere nearly half of the land surface is seasonally covered by snow (Frei and Robinson, 1999). Although the albedo of snow depends on the snow grain size, both of which tend to increase as the snow ages Wuttke et al, 2006), at UV wavelengths the observed decrease in the snow albedo with age is dominantly caused by absorbing contaminants, such as desert dust and carbon soot Warren and Wiscombe, 1980;Chýleck et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vast regions experience seasonal snow: in the Northern Hemisphere nearly half of the land surface is seasonally covered by snow (Frei and Robinson, 1999). Although the albedo of snow depends on the snow grain size, both of which tend to increase as the snow ages Wuttke et al, 2006), at UV wavelengths the observed decrease in the snow albedo with age is dominantly caused by absorbing contaminants, such as desert dust and carbon soot Warren and Wiscombe, 1980;Chýleck et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the effective surface albedo decreases gradually during the transition, and furthermore, the surface albedo of the heterogeneous region depends strongly on the solar zenith angle as well as on the viewing angle. Arola et al (2003) established a model for the effective surface albedo as a function of snow depth. The model involves a saturation level of the surface albedo, that is reached when low vegetation is completely covered by snow.…”
Section: Introductionmentioning
confidence: 99%
“…In SNICAR-online (Flanner et al, 2007), the underlying ground albedo influences the reflectance of a relatively thin snowpack, but density and effective grain size also determine the influence of underlying ground. In the Arola et al (2003) work on satellite respectivity versus snow depth (Fig. 1 in their paper), the respectivity of a 0.02 m (2 cm) snow depth is marginally different from a 0.1 m thick snowpack.…”
Section: Optically Thin Snowpackmentioning
confidence: 99%
“…Also, during snowmelt, the effective surface UV albedo distributions (like those presented in Manninen, 2007, andRobinson andKukla, 1984) are expected to move toward smaller values. We may expect that snow height-dependent parameterizations (like in Arola et al, 2003), in turn, might function well during melt time. Winther (1993) has presented the progress of snow albedo for a Norwegian research site, where the albedo decreased as the snow went under a process of metamorphosis.…”
Section: On the Importance Of Albedo Estimatesmentioning
confidence: 99%
“…From the point of view of the UV radiation measurements, the most important of these are related to sky condition, e.g., clouds and precipitation. The snow depth is recorded, and has been related to surface albedo (Arola et al, 2003a). Continuous radiation measurements are maintained routinely, e.g., global, direct, diffuse and reflected global radiation measurements are available.…”
Section: Ancillary Measurementsmentioning
confidence: 99%